Surface Density of the Spongy and Palisade Parenchyma Layers of Leaves Extracted From Wideband Ultrasonic Resonance Spectra - Alvarez-Arenas, T. E. G.; Sancho-Knapik, D.; Peguero-Pina, J. J.; Gil-Pelegrín, Eustaquio (Frontiers in Plant Science, 2020)
The wide band and air-coupled ultrasonic resonant spectroscopy together with a modified Simulated Annealing metaheuristic algorithm and with a 1D layered acoustic-model are used to resolve the structure of plant leaves. In particular, this paper focuses on the extraction of the surface density of the different layers of tissue in leaves having a relatively simple structure. There are three main reasons to select the surface density as the focus of this study: i) it is a parameter directly extracted by the proposed technique and it requires no further processing, ii) it is relevant in order to study the dynamic of the water within the different tissues of the leaves and also to study the differential development of the different tissues, iii) unlike other parameters provided by this technique (like resonant frequency, impedance, ultrasonic elastic modulus or ultrasonic damping), this parameter can be easier to understand as it is a measure of mass per unit surface. The selection of leaves with a simple structure is justified by the convenience of avoiding an unnecessary complication of the data extraction step. In this work, the technique was applied to determine the surface density of the palisade and spongy parenchyma layers of tissue of Ligustrum lucidum, Vitis vinifera and Viburnum tinus leaves. The first species was used to study the variation of the surface density at full turgor with the thickness of the leaf, while the two other species were used to study the variation of the surface densities with the variation in the leaf relative water content. Consistency of the results with other conventional measurements (like overall surface density, and cross-section optical and cryo-SEM images) is discussed. The results obtained reveal the potential of this technique; moreover, the technique presents the additional advantage that can be applied in-vivo as it is completely non-invasive, non-destructive, fast and equipment required is portable.